2013
DOI: 10.1017/s1047951113001030
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy: prognostic factors and survival analysis in 128 Egyptian patients

Abstract: At our Egyptian tertiary care centre, hypertrophic cardiomyopathy has a relatively worse prognosis when compared with reports from Western and Asian series. Infants have a worse outcome than children presenting after the age of 1 year. A poorer prognosis in childhood hypertrophic cardiomyopathy is predicted by an extreme left ventricular hypertrophy, the presence of sinus tachycardia, and supraventricular tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
1
25
0
2
Order By: Relevance
“…Six studies evaluated the predictive value of NSVT detected during ambulatory electrocardiographic (ECG) monitoring for SCD 12,15,19,20 or CVD 17,22 . Two found a significant relationship between NSVT and SCD 12,15 , with a further study reporting non-significance of NSVT but significance for inducible VT during an electrophysiology study (EPS) 19 .…”
Section: Non-sustained Ventricular Tachycardia (Nsvt)mentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies evaluated the predictive value of NSVT detected during ambulatory electrocardiographic (ECG) monitoring for SCD 12,15,19,20 or CVD 17,22 . Two found a significant relationship between NSVT and SCD 12,15 , with a further study reporting non-significance of NSVT but significance for inducible VT during an electrophysiology study (EPS) 19 .…”
Section: Non-sustained Ventricular Tachycardia (Nsvt)mentioning
confidence: 99%
“…Two found a significant relationship between NSVT and SCD 12,15 , with a further study reporting non-significance of NSVT but significance for inducible VT during an electrophysiology study (EPS) 19 . No studies reported a significant association of NSVT and CVD 17,22 .…”
Section: Non-sustained Ventricular Tachycardia (Nsvt)mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the mean life expectancy of patients who survived into young adulthood does not markedly differ from that of the normal population 12 , sudden cardiac death is common in young adults with HCM, particularly athletes 13 , and some patients develop severe systolic dysfunction and heart failure. Less known is that neonatal forms of HCM rapidly evolve into systolic heart failure and death within the first year of life [14][15][16][17][18][19][20] . Some of these infants have homozygous or compound heterozygous frameshift MYBPC3 mutations 14,[16][17][18][19][20] , expected to result in low level or absence of mutant cMyBP-C.…”
mentioning
confidence: 99%